Heterologous Expression of the Constitutive Disease Resistance 2 and 8 Genes from Poncirus trifoliata Restored the Hypersensitive Response and Resistance of Arabidopsis cdr1 Mutant to Bacterial Pathogen Pseudomonas syringae - Xiaobao Ying; Bryce Redfern; Frederick G. Gmitter; Zhanao Deng (Plants, 2020)
Huanglongbing (HLB), also known as citrus greening, is the most destructive disease of citrus worldwide. In the United States, this disease is associated with a phloem-restricted bacterium, Candidatus Liberibacter asiaticus. Commercial citrus cultivars are susceptible to HLB, but Poncirus trifoliata, a close relative of Citrus, is highly tolerant of HLB. Isolating P. trifoliata gene(s) controlling its HLB tolerance followed by expressing the gene(s) in citrus is considered a potential cisgenic approach to engineering citrus for tolerance to HLB. Previous gene expression studies indicated that the constitutive disease resistance (CDR) genes in P. trifoliata (PtCDRs) may play a vital role in its HLB tolerance. This study was designed to use Arabidopsis mutants as a model system to confirm the function of PtCDRs in plant disease resistance. PtCDR2 and PtCDR8 were amplified from P. trifoliata cDNA and transferred into the Arabidopsis cdr1 mutant, whose resident CDR1 gene was disrupted by T-DNA insertion. The PtCDR2 and PtCDR8 transgenic Arabidopsis cdr1 mutant restored its hypersensitive response to the bacterial pathogen Pseudomonas syringae pv. tomato strain DC3000 (Pst DC3000) expressing avrRpt2. The defense marker gene PATHOGENESIS RELATED 1 (PR1) expressed at much higher levels in the PtCDR2 or PtCDR8 transgenic cdr1 mutant than in the non-transgenic cdr1 mutant with or without pathogen infection. Multiplication of Pst DC3000 bacteria in Arabidopsis was inhibited by the expression of PtCDR2 and PtCDR8. Our results showed that PtCDR2 and PtCDR8 were functional in Arabidopsis and played a positive role in disease resistance and demonstrated that Arabidopsis mutants can be a useful alternate system for screening Poncirus genes before making the time-consuming effort to transfer them into citrus, a perennial woody plant that is highly recalcitrant for Agrobacterium or biolistic-mediated transformation.